Effect of Ba and Zn doping in Bi2Pb0.6Sr2Ca2Cu3Oδ superconductors using ac susceptibility measurements - Halim, S. A.; Mohamed, S. B.; Azhan, H.; Khawaldeh, S. (Springer, 1999)
Ac complex susceptibility, χ = χ′ - iχ″, measurements were done on the samples doped with barium and zinc (Bi2Pb0.6Sr2Ca2-xMxCu3Oδ, M = Ba, Zn and x = 0.02 and 0.10). The data of χ′ shows that coupling of the grains in Zn-doped samples are weaker than that of Ba-doped samples and hence it could be concluded that Zn-doped samples are dominated by the S-I-S type of weak links, whereas the Ba doped samples are dominated by the S-N-S weak links. Calculated values of I0 is three times higher in the Ba doped samples such that the values of Josephson coupling energy, Ej is four times that of Zn doped samples. Analysis based on the sensitivity of the data of dχ′(T)/dT versus temperature furnished further information on the two-step transitions related to the coupling of the grains in both systems.